in brief - Grigoryeva, Elena (project baikal, 2025)
The second half of 2025 is marked by striking architectural events: Days of Architecture in Novosibirsk and Omsk and the XXV anniversary festival «ZVS» in Irkutsk (see a separate block of materials in this issue of PB).
Keywords: Omsk; Novosibirsk; Irkutsk House of Architects